Revenue Implications of Trade Liberalization - Gropp, Reint (Occasional Papers; Occasional Paper ;, 1999)
The apparent contradiction between trade liberalization and continuing high trade tax revenue raises the important question of how, precisely, the one affects the other. Although policymakers generally recognize the long-term benefits of trade liberalization, some have argued for at least a slower pace, in part because of revenue concerns. This paper seeks to address these issues in three complimentary ways: through an overview of the factors that may have a bearing on the question, through a review of trends in trade tax revenue both globally and in selected countries, and through econometric analysis.